Actor engagement as a base for value co-creation in service ecosystem : case study of future electricity demand-side response service for households - Puikkonen, Marjo (2019)
This thesis focuses on exploring the value co-creation in the future electricity demand-side response (DSR) service for households. DSR service is implemented as a cloud service, where high-power home appliances are switched off, if there are consumption overload in the power grid and the flexibility is needed. The service is necessary, especially when the use of electric cars increases. As electricity consumption is expected to increase, it creates challenges for electricity network capacity. Increased production in the near future, as well as moving towards more carbon-neutral production mode, will increase the challenges for the adequacy of electricity. With this service, it is possible to equalize the consumption of electricity with periods of household consumption. However, it is challenging to get households into this DSR service. This opened the possibility of exploring further how users can be engaged to the service. The problem was solved through the operator's commitment, exploring the factors that affected the use of the service. The study was carried out as a qualitative case study, which dealt with the future electricity market and its DSR service. The data was collected through interviews (= 24), utilizing a special Laddering technique. From the responses the graphical thematic maps were created describing the most important things the respondents experienced. The data included the attributes, consequences and values with relationships between them. Respondents felt that the most important features related to the user’s opportunity to participate in the service, the availability of the service and the production of a common good through the service. The most important value factors were own and others well-being, the economy and the well-being of the environment. As a base theory for this study, actor engagement, value co-creation and value co-destruction were found most suitable. Based on this framework built on the theory, a solution was developed for the research problem. Also, the possibility to value co-destruction in this context was presented. Describing the service ecosystem helped to understand the field of action, thus creating a com- prehensive description of the phenomenon.